Reaction of Some Stable Dibenzyltellurium(IV) Derivatives with 1,3-Diaminopropane and 1,2-Diaminopropane - Srivastava, Shekhar; Kumar Soni, Dilip (Asian Journal of Chemistry, 2010)
Ten complexes of tellurium(IV) of the type (C6H5CH2)2TeX2·L (Where X =I–, CN–, NCS–, IO3– and NO3–; L = 1,3-diaminopropane and 1,2-diaminopropane) have been synthesised and characterised.